2015
DOI: 10.1371/journal.pone.0137303
|View full text |Cite
|
Sign up to set email alerts
|

Playing 20 Questions with the Mind: Collaborative Problem Solving by Humans Using a Brain-to-Brain Interface

Abstract: We present, to our knowledge, the first demonstration that a non-invasive brain-to-brain interface (BBI) can be used to allow one human to guess what is on the mind of another human through an interactive question-and-answering paradigm similar to the “20 Questions” game. As in previous non-invasive BBI studies in humans, our interface uses electroencephalography (EEG) to detect specific patterns of brain activity from one participant (the “respondent”), and transcranial magnetic stimulation (TMS) to deliver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…Zhao et al transfected animals with ChABC expressing lentiviral vectors and found better recovery [367]. In 2012, Starkey et al showed that ChABC promoted compensatory sprouting of remaining corticospinal axons and improved forelimb function after unilateral pyramidotomy [308]. In 2015, Mondello et al found that 4 weeks of ChABC treatment promoted earlier recovery in cats after SCI [232].…”
Section: Proteoglycansmentioning
confidence: 99%
“…Zhao et al transfected animals with ChABC expressing lentiviral vectors and found better recovery [367]. In 2012, Starkey et al showed that ChABC promoted compensatory sprouting of remaining corticospinal axons and improved forelimb function after unilateral pyramidotomy [308]. In 2015, Mondello et al found that 4 weeks of ChABC treatment promoted earlier recovery in cats after SCI [232].…”
Section: Proteoglycansmentioning
confidence: 99%
“…In our experiments, a total of 72 bits were transferred on average per subject in approximately 60 min; to our knowledge, this is both the largest CBI information transfer using TMS [superior to Rao et al (2014) and Stocco et al (2015)] as well as the largest CBI bit-rate to date. The type of information delivered to the brain was, however, quite restricted.…”
Section: Resultsmentioning
confidence: 92%
“…If the subject did not perceive a phosphene by the 75% mark, a new location was examined. Based on the results of Stocco et al (2015), the first stimulation site examined was 2 cm dorsal, 1 cm left of the inion. Subsequent sites were then examined at increasing distance from this starting point.…”
Section: Determination Of Phosphene Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations